Mutations in NPHS1 and PLCE1 (NPHS3) in two Vietnamese patients with conginetal nephrotic syndrome - Lien, Nguyen Thi Kim; Van Dem, Pham; Thu Huong, Nguyen; Minh Dien, Tran; Huy Hoang, Nguyen; Thi Quynh Huong, Nguyen (Vietnam Journal of Biotechnology, 2020)
Congenital nephrotic syndrome (CNS), a genetic disease caused by the mutations in genes on autosomes,is usually occurs in the first three months after birth. The mutations in genes that encode for the structural andfunctional proteins of podocytes lead to loss of the function of glomerular filtration. So far, a number of genesrelated to the disease have been identified such as: NPHS1, NPHS2, PLCE1 (NPHS3), ACTN4, CD2AP, INF2and WT1. In this article, we amplified all of exons in NPHS1 and PLCE1 genes of two Vietnamese patientswith CNS and members of patients’ family. PCR products were purified and sequenced directly on automaticsequencer ABI 3500 Bio System (USA). The sequencing results were compared with the sequences of NPHS1and PLCE1 genes published in the Ensembl database (ENSG00000161270 and ENSG00000138193,respectively) by using BioEdit software to detect mutations. We identified two mutations: c.2398C>T(p.Arg800Cys, exon 18), c.3315A>G (p.Ser1105Ser, exon 26) in NPHS1 gene and two mutations: c.5330 C>T(p.Thr1777Ile, exon 23), c.5780A>G (p.His1927Arg, exon 25) in PLCE1 gene in study patients. These twopatients carried simultaneously the mutations in the NPHS1 and PLCE1 genes with serious phenotype. Theresults of our study might be evidences for the role of mutations in NPHS1 and PLCE1 genes in thedevelopment of disease in patients. These are useful information in identifying the cause of disease and providethe genetic counseling to the patients’ family.